A visibilidade e representação social das religiões nos selos postais brasileiros (The visibility and social representations of religions in Brazil postage stamps).DOI: 10.5752/P.2175-5841.2012v10n25p233 - Salcedo, Diego Andres; Bronsztein, Karla Patriota (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Este trabalho analisa a forma com a qual o selo postal brasileiro contribuiu para a construção de representações da religião católica em relação a outras práticas religiosas. Foi considerado, para isso, a concepção deste artefato enquanto media, texto semiótico e sua estreita relação com o discurso religioso. O corpus é composto por selos postais comemorativos brasileiros emitidos durante o século XX. A sua identificação e análise foi feita a partir do catálogo RHM. Entre o ano de 1900 e 2000, os Correios emitiram 2354 selos postais do tipo comemorativo. A partir da observação e identificação de recorrências religiosas foram compilados 222 selos postais comemorativos. O estudo correlacionou a recorrente temática religiosa com o contexto histórico brasileiro, considerando o declínio do catolicismo como maioria religiosa no país e às representações das práticas religiosas nas mídias. A conclusão indica a influência da Conferência Nacional dos Bispos do Brasil, junto ao Ministério das Comunicações e dos Correios do Brasil, consagrando e enaltecendo a visibilidade de personalidades, eventos e a práxis católica, como um discurso único e superior às demais práticas religiosas. <!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Abstract This paper analyses the way in which postal Brazilian stamps have contributed to the construction of representations of the catholic religion regarding other religious practices. In this sense, the conception of these stamps was taken into account as media, semioptical texts in close relation with the religious speech. The corpus is composed by postal commemorative Brazilian stamps issued during the twentieth century. The identification and analyzes of the stamps were made through RHM catalogue. Between the year of 1900 and 2000, the Brazilian post offices issued 2.354 commemorative postage stamps. From the observation and identification of religious recurrences 222 commemorative stamps were compiled. The study correlated the recurring religious theme with the historical Brazilian context, taking into account the decline of the Catholicism as the major religion in Brazil and also the representations of the religious practices in the media. The conclusion of this paper indicates the influence of the National Conference of the Bishops of Brazil regarding the Ministry of the Communications, establishing and enforcing the visibility of Brazilian personalities, events, and also of catholic practices taken as special and superior in comparison with other religious practices. Key-words: Brazil; Religion; Postage Stamps; Social Representation; Visibility.